Validação do diagnóstico de enfermagem recuperação cirúrgica retardada - Appoloni, Aline Helena (Universidade Federal de São Carlos, 2011)
The postoperative period requires the nursing team to be prepared to deal with possible specific complications. The precision of the nursing diagnosis during that period is essential for ensuring an effective and decisive care plan. The postoperative recovery may be changed, causing it to be delayed and, therefore, to require specific nursing intervention. The human response is represented by NANDA-I, through the Delayed Surgical Recovery (DSR) diagnosis. Based on the analysis of the elements of the DSR diagnosis, the possibility of gaps may be considered, especially gaps that are related to the defining characteristics (DC) and the related factors (RF). This study aimed at analyzing the concept and validation (by experts) of the Delayed Surgical Recovery nursing diagnosis, which is proposed by NANDA-I. That is a descriptive validation study of a nursing diagnosis, based on the model that was proposed by Hoskins. A bibliographical review was accomplished on LILACS, PubMed, CINAHL and Cochrane Library databases, in order to select studies that are related to the theme, for to ground the concept analysis, performed according to the Walker and Avant model, which describe an investigation process on basic elements of an eight-step concept. Fifty-seven studies were elected to conduct the concept analysis. Posteriorly, a content validation of the nursing diagnosis was made according to the Fehring model, in which the opinion of experts is surveyed, regarding the adequacy of the DSR nursing diagnosis. The DSR concept is found to be used in medicine, followed by nursing, psychology, social service, speech therapy, nutrition and physical therapy. DSR is usually discussed in relation to the deterioration of physical, psychological and social functioning interrelationship of patients and their relatives. The identified main defining attributes were: impaired ability to walk, need for help to perform daily activities, difficulty in performing selfcare, difficulty in reassuming social roles, persistent fatigue, necessity of a longer time for recovery, and others. Among the identified background items, there were: pain, anxiety, negative experiences on previous surgeries, infection, and others. The main consequences were: rehospitalization, prolonged hospitalization, depression, and others. Given the concept analysis data, some modifications on the enunciation and definition of DSR diagnosis were suggested, as well as some modifications on the Defining Characteristics (among them: delays the return to social activities and persistent pain ), and some suggestions for including DC (such as need for help to perform daily activities , cardiovascular and pulmonary problems ). The inclusion of Related Factors as advanced age , problems arising from anesthesia and presence of comorbidities were also suggested. The elements of the nursing diagnosis and the proposed modifications after the concept analysis were subjected to the review of 45 experts. As a result, changes were made on the diagnosis enunciation text which was modified to Postoperative Delayed Recovery. The nursing diagnosis definition text was changed to extension of the number of days of mediate or delayed postoperative to resume activities that sustain life, health and welfare , validation of the DC proposed by NANDA-I, modification of the DC text, such as Delays the return to social work, job, familiar, study, religious activities, etc. , Loss of appetite , Postoperative persistent pain and Persistent fatigue . Yet, it was possible to add six DCs for suggestion to be included in the Nursing Diagnosis of NANDA-I need for help to perform daily activities , Cardiovascular problems and Pulmonary problems were the ones that received the highest scores. As for the RF, all the ones that were presented by NANDA-I were validated and seven new RF were suggested to be included. Among the ones that received the highest scores by the experts are: Problems arising from anesthesia , Presence of comorbidities , Compromised nutritional conditions and Advanced age . The identified results offer the possibility of reviewing the DSR diagnosis by NANDA-I, contributing to knowledge about postoperative period and, consequently providing a better quality of nursing care to surgical patients who experience delayed recovery.
Validation of the Delayed Surgical Recovery nursing diagnosis.
Keywords: Enfermagem cirúrgica; Diagnóstico de enfermagem; Estudos de validação; Pós-operatório; Recuperação da função fisiológica; Enfermagem cirúrgica; Nursing diagnosis; Validation studies; Postoperative period; Recovery of physiological function; CIENCIAS DA SAUDE::ENFERMAGEM